Cytotoxicity of Two Experimental Epoxy Resin-Based Sealers - Ashraf, Hengameh; Najafi, Farhood; Heidari, Soolmaz; Yadegary, Zahra; Zadsirjan, Saeede (Iranian Endodontic Journal, 2018)
Introduction: Many endodontic sealers are available, but search for the ideal sealer continues. This study aimed to assess the cytotoxicity of two experimental endodontic sealers in comparison with AH-26 resin sealer. Methods and Materials: This in vitro study was conducted on conventional and experimental root canal sealers: AH-26, an epoxy resin experimental sealer A (ES-A) composed of calcium tungstate, zirconium oxide, aerosil, bismuth oxide, titanium oxide, hexamine and an epoxy resin and experimental sealer B (ES-B) with compositions similar to ES-A except for the presence of imidazoline as a catalyst. The experimental sealers containing nano-particles were mixed with 37.5% of an epoxy resin. The extraction of five samples of each experimental sealer (A, B) and AH-26 sealer were subjected to MTT assay in the form of set and fresh at 1, 24 and 72 h with 1, 10, 100% dilution according to the International Standard ISO:10993-2012. Data were analyzed using the one-way ANOVA. Results: The set ES-A had the least cytotoxicity from the first hour but the cytotoxicity of ES-B and AH-26 extraction decreased over time. In fresh form, except for 100% concentration, ES-A showed the least cytotoxicity compared to the other two sealers. Conclusion: All three sealers had high cytotoxicity in 100% concentration but had low cytotoxicity in 10% and 1% concentrations. Keywords: Cytotoxicity; Endodontics; Epoxy Resin; Sealer